ZIF-8 and Its Magnetic Functionalization as Vehicle for the Transport and Release of Ciprofloxacin - Ventura Castillo Ramos; Cinthia Berenice García Reyes; Guillermo Mangas García; María Inmaculada Sampedro Quesada; Fernando José Martínez-Checa Barrero; Jacob Josafat Salazar Rábago; Manuel Sánchez Polo (MDPI AG, 2022)
The use of nanomaterials for the controlled release of drugs aims to enhance their effectiveness, especially when poorly soluble in water, and achieve their rapid, localized, and effective administration. The present study focuses on the use of a Zeolitic Imidazolate Framework-8 (ZIF-8) as vehicle for the transport and controlled release of the antibiotic ciprofloxacin (CIP) as model due to its favorable physicochemical characteristics. The objective is to synthesize the ZIF-8 material loaded with CIP through encapsulation for subsequent release of the drug in neutral and acid physiological media. In addition, functionalization of the CIP/ZIF compound with magnetic nanoparticles (NP) was sought to increase its traceability through the possible use of magnetic fields. Characterizations by XRD, FT-IR, SEM-EDX, and TGA showed a satisfactory synthesis of both pure ZIF-8 and ciprofloxacin-loaded ZIF-8, with high crystallinity and thermal stability. The release profiles showed an abrupt initial release that stabilized over time. A much higher release (20-80% greater) was obtained in acid versus neutral pH in all cases, attributable to the collapse of the ZIF-8 structure in acid media. In addition, functionalization of the material with iron NPs did not affect the behavior of the system during drug release. Antimicrobial activity tests against E. coli and S. aureus showed that ZIF-8 per se exerts antimicrobial activity, while the compounds CIP/ZIF and magnetic CIP/ZIF increased the antimicrobial capacity of pure CIP by 10-20%. The ZIF-8 system has high potential as a drug carrier and release agent for the treatment of diseases, especially those that cause acidification of the cellular environment, achieving a rapid, localized, and targeted action with the possibility of achieving traceability of the system after its magnetic functionalization.